The influence of alignment on risk of knee osteoarthritis progression according to baseline stage of disease - Cerejo, Rui; Dunlop, Dorothy D.; Cahue, September; Channin, David; Song, Jing; Sharma, Leena (Arthritis and rheumatism, 2002)
Objective Varus and valgus malalignment increase the risk of medial and lateral osteoarthritis (OA) progression, respectively. The impact of a mechanical factor such as alignment depends not only on the factor itself, but also on the state of the joint. The less‐damaged joint of mild OA may be less vulnerable to malalignment effects than the more‐damaged joint of moderate OA. Our goal was to explore the impact of alignment on subsequent progression of knee OA according to the baseline stage of disease. Methods Two hundred thirty patients with knee OA (defined by the presence of osteophytes and symptoms) recruited from the community underwent assessment of both lower limbs at baseline and at an 18‐month followup. Alignment was measured on a full‐limb radiograph as the angle made by the intersection of the femoral and tibial mechanical axes. Compartment‐specific progression was defined as an increase between baseline and 18 months in the grade of severity of joint space narrowing on radiographs of semiflexed knees taken after fluoroscopic confirmation of position. Knees were grouped according to their baseline stage of OA as Kellgren/Lawrence (K/L) grades 0–1, 2, or 3. Progression odds ratios were estimated from logistic regression using generalized estimating equations. Results There were 377 K/L grade 0–3 knees in 230 subjects (173 women and 57 men, mean age 64.0 years, mean body mass index 30.4 kg/m2) in this longitudinal study. In knees with mild OA (K/L grade 2), the odds of 18‐month progression in the medial compartment were significantly increased 4‐fold by varus alignment at baseline. In K/L grade 2 knees, the odds of lateral progression were increased 2‐fold by valgus alignment (approaching significance). In knees with moderate OA (K/L grade 3), the risk of progression was comparably increased by varus or valgus alignment (10‐fold). Conclusion While some effect of malalignment was suggested at almost all stages of knee OA examined, the impact of varus or valgus malalignment on the odds of OA progression over the ensuing 18 months was greater in knees with moderate (K/L grade 3) OA at baseline, possibly due to greater joint vulnerability with some contribution from slightly more severe malalignment.